Dynamic spreading characteristics of droplet impinging soybean leaves - Li, He; Niu, Xiaoxiao; Ding, Li; Tahir, Ali Shahid; Guo, Changle; Chai, Jiajun; Zhang, Kaifei; Cheng, Shangshang; Zhao, Yiqiu; Zhang, Yahui; et al. (International Journal of Agricultural and Biological Engineering, 2021)
The study on the deposition efficiency of pesticide droplets on soybean leaves can provide the basis for reducing pesticide quantity and increasing pesticide efficiency during the application of soybean plant protection machinery. The movement behavior of droplet impinges on the plant leaf surface is affected by many factors, among which the most important and the easiest to adjust are spray droplet size and impingement velocity. By changing the droplet size and impact velocity and using Fluent simulation software, the pesticide droplet hitting the soybean leaf surface was simulated and a test platform was established to verify the simulation results. The conclusions are as follows: The longitudinal roughness of soybean leaves is higher than the transverse roughness, the longitudinal pressure of soybean leaves is higher than the transverse pressure during the impact process, and the velocity of droplet spreading along the longitudinal is lower than that of spreading along the transverse; although soybean leaf surface has high adhesion, droplet losses still exist when droplet impact velocity is relatively high. The maximum spreading diameter of the droplet increases first and then decreases with the increase of impact velocity. At the same time, the maximum spreading diameter of droplet increases with the increase of particle size. The droplet deposition was best at 1.34 m/s impact velocity and 985 μm particle size. This conclusion can provide optimal operation parameters for soybean plant protection operation which can be used to guide soybean plant protection operation, improve control effect, reduce quantity and increase efficiency. Keywords: soybean, deposition efficiency, Fluent, droplet impact, spreading features, dynamic DOI: 10.25165/j.ijabe.20211403.6274 Citation: Li H, Niu X X, Ding L, Tahir A S, Guo C L, Chai J J, et al. Dynamic spreading characteristics of droplet impinging soybean leaves. Int J Agric & Biol Eng, 2021; 14(3): 32–45.